Finland’s Policy towards the Russian Federation under M. Ahtisaari (1994–2000): A Cognitive Approach - D. G. Romanov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The paper examines views of the President of Finland Martti Ahtisaari on the development of the Russian-Finnish relations in 1994–2000. This issue has been thoroughly studied by both Russian and Western scholars, both in terms of bilateral relations and within a broader framework of Finland’s foreign policy in a post-bipolar world. This paper, however, attempts to address the issue from the perspective of a cognitive approach. According to the author, this approach may not only provide insights on the models of thinking of M. Ahtisaari, who played a key role in the formation of Finland’s foreign policy in 1994–2000, but also to reassess the dominant views by placing them within a new theoretical framework. To this end, the paper provides a cognitive mapping of a sample of speeches and articles written by the President of Finland in 1994–2000. The author identifies the most significant and pronounced themes specific to M. Ahtisaari’s foreign policy discourse, and establishes causal links between them. On that basis the author creates a cognitive map which in turn makes it possible to detect the central causal line: a set of closely related themes and ideas which provided a general framework that defined president Ahtisaari’s views on policy towards Russia. The subsequent analysis of the cognitive map reveals a hierarchical system of the key objectives and determinants in the M. Ahtisaari foreign policy agenda setting. The cognitive mapping shows that during M. Ahtisaari’s presidency the main goal of Finland’s foreign policy towards the Russian Federation was to promote peace and security in Europe in general and in the Northern Europe and the Baltic Sea region in particular. In that regard special attention was paid to the Northern Dimension programme. It was considered as a primary means of the EU-Russia rapprochement aimed at enhancing political dialogue and increasing economic cooperation between them, as well as at promoting reforms in the post-Soviet Russia.